Heat shock transcription factor 1 is SUMOylated in the activated trimeric state - Kmiecik, Szymon; Drzewicka, Katarzyna; Melchior, Frauke; Mayer, Matthias P. (The journal of biological chemistry, 2021)
The heat shock response is a transcriptional program of organisms to counteract an imbalance in protein homeostasis. It is orchestrated in all eukaryotic cells by heat shock transcription factor 1 (Hsf1). Despite very intensive research, the intricacies of the Hsf1 activation-attenuation cycle remain elusive at a molecular level. Post-translational modifications belong to one of the key mechanisms proposed to adapt the Hsf1 activity to the needs of individual cells, and phosphorylation of Hsf1 at multiple sites has attracted much attention. According to cell biological and proteomics data, Hsf1 is also modified by small ubiquitin-like modifier (SUMO) at several sites. How SUMOylation affects Hsf1 activity at a molecular level is still unclear. Here, we analyzed Hsf1 SUMOylation in vitro with purified components to address questions that could not be answered in cell culture models. In vitro Hsf1 is primarily conjugated at lysine 298 with a single SUMO, though we did detect low-level SUMOylation at other sites. Different SUMO E3 ligases such as protein inhibitor of activated STAT 4 enhanced the efficiency of in vitro modification but did not alter SUMO site preferences. We provide evidence that Hsf1 trimerization and phosphorylation at serines 303 and 307 increases SUMOylation efficiency, suggesting that Hsf1 is SUMOylated in its activated state. Hsf1 can be SUMOylated when DNA bound, and SUMOylation of Hsf1 does neither alter DNA-binding affinity nor affects heat shock cognate 71kDa protein (HSPA8)+DnaJ homolog subfamily B member 1-mediated monomerization of Hsf1 trimers and concomitant dislocation from DNA. We propose that SUMOylation acts at the transcription level of the heat shock response.